2011
DOI: 10.1590/s0001-37652011005000018
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-anatomical features of underground systems in six Asteraceae species from the Brazilian Cerrado

Abstract: In the Brazilian Cerrado (neotropical savanna), the development of bud-bearing underground systems as adaptive structures to fire and dry periods can comprise an important source of buds for this ecosystem, as already demonstrated in the Brazilian Campos grasslands and North American prairies. Asteraceae species from both woody and herbaceous strata have subterranean organs that accumulate carbohydrates, reinforcing the adaptive strategy of these plants to different environmental conditions. This study aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 34 publications
1
36
0
12
Order By: Relevance
“…In the state of São Paulo, Almeida et al (2005) performed a survey on Asteraceae species found in eight localities of Cerrado sensu stricto and emphasized the need for further studies on the herbaceous-subshrubby flora in these fragments, in which many were sole species and exclusive, considering the conservation of these areas as fundamental. Among the different Asteraceae tribes listed in this study, Vernonieae was the one with the highest number of species; Appezzato-da- Glória et al (2008) reported the presence of different thickened underground organs in two frequent species in the state of São Paulo Cerrado inside this tribe. In Lessingianthus bardanoides (Less.)…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…In the state of São Paulo, Almeida et al (2005) performed a survey on Asteraceae species found in eight localities of Cerrado sensu stricto and emphasized the need for further studies on the herbaceous-subshrubby flora in these fragments, in which many were sole species and exclusive, considering the conservation of these areas as fundamental. Among the different Asteraceae tribes listed in this study, Vernonieae was the one with the highest number of species; Appezzato-da- Glória et al (2008) reported the presence of different thickened underground organs in two frequent species in the state of São Paulo Cerrado inside this tribe. In Lessingianthus bardanoides (Less.)…”
Section: Introductionmentioning
confidence: 66%
“…H. Rob., the thickened underground organ is represented by a xylopodium and in Chresta sphaerocephala DC., by a diffused underground system of radicular structure that produces aerial stems (Appezzato-da-Glória et al, 2008). This underground system is an important vegetative reproduction device in the Cerrado flora.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffuse underground systems may bear buds (Appezzatoda- Glória et al 2008) and contribute to clonal reproduction, which is an important feature in ecosystems with limited resources and/or that experience climatic limitations (Couteron et al 2014). As diffuse systems grow to occupy a large space, they can come to represent a strong sink for photoassimilates, not only due to the demands of growth but also for storage, which, in the case of C. exsucca, occurs mainly as fructans (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Brazilian species from this genus occur mainly in the Cerrado regions in climates that have dry winters (Magenta et al, 2010), and these species are most often observed under such conditions that may be related to the type of thickened underground system, which supports the plants' water needs during dormancy (Zaidan and Carreira, 2008;Magenta et al, 2010) and is essential for regenerating the vegetative aerial portions (Oliveira et al, 2013;Bombo et al, 2014). The thickened underground systems, which can bear buds, were observed in other Asteraceae species, and these systems may be morphologically diverse, such as xylopodia, rhizophores, root buds and diffuse underground systems (Vilhalva and Appezzato-da-Glória, 2006;Hayashi and Appezzato-da-Glória, 2007;Appezzato-da-Glória et al, 2008;Appezzato-da-Glória and Cury, 2011). However, it has been observed that some species cannot propagate vegetatively even bearing a thickened underground system, and the sexual reproduction ensures maintenance of the species (Cury et al, 2010).…”
Section: Introductionmentioning
confidence: 99%